Studi Ekologi Lanskap Di Sekitar Sarang Burung Pemangsa Di Kawasan Telaga Warna - Susanti Withaningsih (Jurnal Pro-Life, 2017)
Raptors are considered biologically important, environmentally sensitive and indicators of the health of the ecosystem. Breeding period is a critical phase for raptors that at present are categorized as rare and threatened species Nest site selection can have important nesting success consequences in raptors.. In relation to this, a spatial analysis has been undertaken to assess the relationship between landscape structure and the presence of predators’ nests in the landscape of Telaga Warna, Kabupaten Bogor - West Java Indonesia. The methods used in the study are the qualitative method by using descriptive analysis and the quantitative one by applying the Fragstat version 2.0. The study used four circular buffer at distances of 250, 500, 750 and 1000m around each nest-tree to analyze the relationship between raptor nest occurrence and landscape structure. The result suggests that the landscape of Telaga Warna is a mosaic consisting of natural and artificial vegetation of different structure. The three species of raptors tend to select a nesting site that has low degree of landscape contrast at distance of 250 m around nest. However, in terms of landscape complexity, there is not great difference among the nesting sites at distance of 250m. Edge density around black eagle nest is higher compare the other nest at distance of 250-1000 m. Prey density is high and distributed at seven hunting area at Telaga Warna. Characteristic differences in nest site selection may be due to landscape structure at different scales around the nest.Keyword : landscape, raptor, nest